Advanced technology in glycemic control and prevention of diabetes mellitus complications - Elena V. Biryukova (LLC "MEDIAFORMAT", 2023)
The review is focused on the issues of blood glucose self-monitoring for prevention of the diabetes mellitus complications. The data of clinical trials and actual clinical practice are provided that demonstrate improved quality of life and carbohydrate metabolism indicators in patients using advanced technology.